Do peers matter? The influence of peers' self-regulation on individual self-regulation: a longitudinal multilevel analysis - Busching, Robert (Frontiers in Developmental Psychology, 2024)
Introduction: Self-regulation is important for social as well as academic success, and research shows that it is also shaped by social interactions. At the same time, peers shape children's development in many domains. Linking these two concepts, it can be predicted that children who are surrounded by peers with a high level of self-regulation later show higher self-regulation themselves compared to those who are surrounded by peers with a low level of self-regulation. Methods To test this assumption, a longitudinal sample with N = 1,658 participants in 181 classrooms (μage = 8.37) was analyzed. The self-regulation facets of working memory updating, inhibition, and flexibility were measured using an age-appropriate version of the Stroop test, the repeat-digits-backward test, and the Wisconsin card-sorting task. Based on this data, a score for both the individual and class level was calculated. Results The results show that the classmates‘ level of self-regulation predicted later individual self-regulation above the individual self-regulation score. While neither age nor gender moderated this relationship, there was a significant cross-level interaction: Especially individuals with a low level of cognitive flexibility gained from being surrounded by peers with a high level of cognitive flexibility. Discussion While the results show that peers constitute an important social context for the development of self-regulation, this fact is often only a minor point in modern self-regulation theories.